Effects of metabolic ergogenic agents on sprinters` anaerobic performance rated by kinetic criteria - Tambovtseva, R. V.; Voytenko, Ju. L.; Pletneva, E. V. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to test benefits of natural beta alanine amino acid administration on the highly skilled sprinters` anaerobic performance, with the model testing experiment run at the Muscular Activity Bioenergy Laboratory of the N.I. Volkov Sports Biochemistry and Bioenergy Department. Sampled for the study were highly skilled sprinters (n=22) split up into Experimental (EG, n=10) and Reference (RG, n=12) Groups. The Experimental Group administered 6g of beta alanine per day for 14 days; and the Reference Group administered placebo (microcrystal cellulose). The anaerobic work efficiency was rated by the following standard tests: maximal anaerobic efficiency (MAE) test by cycle ergometer E894 (made by Monarch company); and Wingate test of the lactate glycolytic capacity rated by the lactic acid concentration in blood in the quiescent state and after training.